Predictors of health related quality of life three years after myocardial infarction with ST segment elevation - Lović, Milan (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Health-related quality of life (HRQoL) is an important indicator of patient condition following myocardial infarction. It may serve as a predictor of mortality and new hospitalization. The aim of this study was to evaluate the association of selected sociodemographic and clinical characteristics with HRQoL in the Serbian cohort of patients with myocardial infarction with ST segment elevation (STEMI) that were treated with primary percutaneous coronary intervention (pPCI). Methods. Patients were recruited from the population of patients with STEMI who were hospitalized in the Clinical Center of Serbia in Belgrade, between 1st December, 2009 and 30th June, 2010. The study was conducted among 507 STEMI patients treated with pPCI. The HRQoL was assessed using the Questionnaire Short Form Health Survey (SF-36). Multivariate logistic regression models were used for each components score in order to determine independent predictors of HRQoL. Results. The patients with the lowest tertiles of Physical component score (PCS) and the Mental component summary score (MCS) were older, likely to be females, unpartnered, with a poor economic status, with diabetes, with prior myocardial infarction and with more extensive coronary artery disease. There were more employed and the individuals with smoking history in the group of patients with the higher scores. The characteristics of patients with lower PCS score were: the higher presence of hypertension, prior cerebrovascular insult and left anterior descending artery as infarct artery. This study demonstrated that HRQoL was significantly associated with patient’s age, gender, diabetes mellitus, a poor way of living and loneliness. Furthermore, the presence of previous cerebrovascular insult seems to affect the physical component score. Conclusion. Knowledge of predictors of HRQoL in the STEMI patients may provide indications for optimal treatment and anticipate their impact on the treatment outcome.